NUTRITIONAL AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF ANDROGRAPHIS LAWSONII GAMBLE - SATHYA, ELAVARASAN; SEKAR, THANGAVEL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Andrographis lawsonii Gamble is a medicinal herb species, Endemic to India: Karnataka (Dakshina kannada or south Canara district), Kerala (Palakkad district), and Tamil Nadu (Coimbatore and Nilgiris districts). The Andrographis is a large genus of the family Acanthaceae. This study focused to check the preliminary phytochemical nutritive analysis, leaf stem and root and gas chromatography-mass spectrometry (GC-MS) analysis leaf methanol extract. Methods: The plant samples were subjected to Soxhlet extraction for phytochemical analysis and further experimental studies. The test on phytochemical studies indicated the presence of alkaloids, saponins, glycosides, and flavonoids glycosides within the plant parts, respectively. The estimation of carbohydrate protein starch methanol leaves extracts to have high activity compared to others. Results: Preliminary phytochemical and Nutritional analysis in A. lawonii. Nutritional analysis in carbohydrate protein and starch content was found to be high in leaf methanol extract. Highly medicinal compound analysis in this GC-MS Analysis 50 compound present in methanol leaf extract. Conclusion: The leaf methanol extract of A. lawsonii has exhibited remarkable preliminary phytochemical analysis and nutritional analysis GC-MS analysis to the medicinal plant.